Effects of Doneness on the Microbial, Nutritional, and Quality Properties of Pork Steak of Different Thicknesses - Jang, Aera (Food Sci Anim Resour, 2019)
This study aimed to evaluate the effect of doneness on the microbial, nutritional, and quality characteristics of 1.5 cm- and 2.0 cm-thick pork neck steaks. Pork neck meat was obtained within 24 h after slaughtering, cut into 1.5 cm- and 2.0 cm-thick slices (n=5), packed in LLD-PE wrap, and stored at 4±2°C for 7–10 days until aerobic plate counts (APC) reach 5.51–6.50 Log CFU/g. Then, the pork meat was cooked on a frying pan till it was medium-rare, medium, or well-done. The microbial inhibition rates of the 1.5 cm- and 2.0 cm-thick steak in medium-rare state were 58.26% and 51.70%, respectively, whereas it was 100% for medium-done pork steak of either thickness. The total calories of the 1.5 cm- and 2.0 cm-thick well-done pork steaks were 643.61 kcal/100 g and 675.00 kcal/100 g, respectively, which was higher than that in medium-rare and medium-done steaks. The retention ratios for Fe and K in the well-done steak were significantly lower than those in the medium and medium-rare steak of either thickness (p<0.05). The shear force of the medium-rare and medium steak did not differ, whereas that of the well-done steak was significantly higher than that of the medium-rare steak of either thickness (p<0.05). We observed that the well-done pork steak had tough texture, low mineral content, and high calories. Therefore, consumption of medium and medium-rare pork is more beneficial than that of well-done pork.